The benefits of handwriting in the development of reading ability: a review of neuroimaging findings - Vlachos, Filippos (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Although reading and writing are often treated as two separate processes, the research data of recent years suggest that these two functions seem to be interrelated and one depends on the other. The aim of this study was to examine whether handwriting is related to and, further, influences the development of reading abilities. To this end, we have reviewed neuroimaging research conducted over the last fifteen years. Research findings, both for pre-school and early-school children, as well as for adults, showed that handwriting influences brain development and activates brain reading systems more than other sensory kinetic techniques. Neuroimaging revealed that learning to write is based on the development of a network of brain structures, which includes the dorsal premotor cortex, the ventral premotor cortex, the upper parietal cortex and the fusiform gyrus of the left hemisphere in right-handed persons, as well as the contralateral cerebellum, structures whose participation and interconnection are specific to the writing of alphabet characters. This network is structured for the common learning of writing and reading and depends on the level of the writer’s experience. The perception of letters is helped by the handwriting experience, upon which the ability to process the letters in the person’s brain during reading is also based. The brain networks that appear to be triggered when identifying letters following the learning of these letters through handwriting are the same sensory kinetic networks that are activated during letter recognition and reading. In conclusion, the sensory experience gained through handwriting seems to develop the brain and strengthens the person’s ability to read.